(untitled) (Journal of Hama University, 2019)
The effect of strengthening continuous reinforced beams on shear using CFRP sheets can be associated by several factors such as the mechanical and dimensions proprieties for sheets, and some of them related to the beam as concrete compressive strength and amount of shear reinforcement. Using Finite Element Method (FEM), and Materially Non-linear Analysis (MNA) is performed to a series of continuous reinforced concrete beams strengthened on shear using CFRP sheets by analytic numerical study. Also, a parametric study has been carried out to study the effect of concrete compressive strength and amount shear reinforcement on shear strengthening of those beams strengthened using CFRP sheets. This research shows that the effect of CFRP in strengthening the continuous reinforced concrete beams on shear increases when the ability of these beams are decreased without strength, This efficiency is increased when the concrete compressive strength used is decreases and when the amount of shear reinforcement are decreases.